Prognostic significance and postoperative chemoradiotherapy guiding value of mean platelet volume for locally advanced esophageal squamous cell carcinoma patients - Zhang, Wei; Jia, Hongyuan; Chen, Xue; Diao, Wei; Leng, Xuefeng; Cao, Bangrong; Wang, Yi; Cheng, Zhuzhong; Wang, Qifeng (Frontiers in Oncology, 2023)
Objective To investigate the predicting prognosis and guiding postoperative chemoradiotherapy (POCRT) value of preoperative mean platelet volume (MPV) in patients with locally advanced esophageal squamous cell carcinoma (LA-ESCC). Methods We proposed a blood biomarker, MPV, for predicting disease-free survival (DFS) and overall survival (OS) in LA-ESCC patients who underwent surgery (S) alone or S+POCRT. The median cut-off value of MPV was 11.4 fl. We further evaluated whether MPV could guide POCRT in the study and external validation groups. We used multivariable Cox proportional hazard regression analysis, Kaplan–Meier curves, and log-rank tests to ensure the robustness of our findings. Results In the developed group, a total of 879 patients were included. MVP was associated with OS and DFS defined by clinicopathological variables and remained an independent prognostic factor in the multivariate analysis (P = 0.001 and P = 0.002, respectively). For patients with high MVP, 5-year OS and 0DFS were significantly improved compared to those with low MPV (P = 0.0011 and P = 0.0018, respectively). Subgroup analysis revealed that POCRT was associated with improved 5-year OS and DFS compared with S alone in the low-MVP group (P < 0.0001 and P = 0.0002, respectively). External validation group analysis (n = 118) showed that POCRT significantly increased 5-year OS and DFS (P = 0.0035 and P = 0.0062, respectively) in patients with low MPV. For patients with high MPV, POCRT group showed similar survival rates compared with S alone in the developed and validation groups. Conclusions MPV as a novel biomarker may serve as an independent prognosis factor and contribute to identifying patients most likely to benefit from POCRT for LA-ESCC.